Numerical study the effect of inlet and outlet ventilation configurations for passive cooling air conditioning system - Safitra, Arrad Ghani; Diana, Lohdy; Pratilastiarso, Joke; Hidayat, Nur (Mechanical Engineering Department - Institut Teknologi Adhi Tama Surabaya, 2024)
The application of Green Energy Technology through Passive Cooling System is the right solution. It aims to achieve energy savings and reduce CO2 emissions. This study focuses on the simulation of room conditions using the computational fluid method. The simulation aims to determine the effect of inlet and outlet configuration against the air condition in the room. The results presented in this simulation are the distribution of air temperature, air humidity, and air velocity. The variations used in the simulation are the air inlet and outlet positions, there are three configurations of air inlet and outlet positions. Variation 1: two inlets – one outlet, Variation 2: two inlets – two outlets, Variation 3: four inlets – three outlets. The results of the study show Variation 3 has the best design if cooling or heating equipment wants to be added, for example passive cooling in summer and a heater for cold weather. On other hand, Variation 1 is the most effective in maintaining the stability of humidity distribution and air velocity within the room. This configuration successfully creates optimal ventilation by generating efficient natural convection without significant fluctuations, achieved using two inlets and one active outlet